Efektivitas Penggunaan E-Modul Dalam Meningkatkan Perilaku Afektif Dan Critical Thinking Skill Mata Pelajaran PPKN di SMPN 1 Bangkalan - Trimurtiningsih, Anni; Eka, Soesiana Tri; Hanifah, Sri Yuni (Penerbit STKIP PGRI Bangkalan, 2024)
Technology and conditions of distance learning, one of the learning media that can be used is the use of electronic modules (e-modules) which are present as an adaptive form of ordinary modules used during direct learning.